A rare case report of anal canal adenocarcinoma. Issue 37 (17th September 2021) - Song, Xiaowei; Zhao, Huimin; Yang, Yongping; Zhao, Linxian; Zhao, Yongqing; Li, Jiannan
Abstract: Rationale: Anal canal adenocarcinoma is a kind of rare malignant tumor of the intestinal tract with a low incidence rate. Patient concerns: A 42-year-old man came to our department with anal tenderness accompanied by intermittent drainage of mucus discharge for 2 weeks. Diagnoses: The computer tomography showed a strip-shaped high-density shadow in the rectal wall. The magnetic resonance imaging showed a cyst-like mass of about 33 × 57 × 30 mm in the anal area. The lesion penetrated the anal canal, and plaque-shaped high signal shadow can be seen in the left side of the anus. The intraoperative pathology indicated the mass as anal canal adenocarcinoma. Interventions: The abdominal perineal resection was performed for this patient. The postsurgical pathology showed that the tumor was anal canal adenocarcinoma with large amounts of mucus. Outcomes: The patient recovered well and was discharged from our department at 12th day post-surgery. This patient received further pelvic radiotherapy. Lessons: Anal canal adenocarcinoma is a kind of malignant tumor that is extremely rare clinically. Computer tomography, magnetic resonance imaging, coloscopy, and histopathology are vital for the diagnosis of anal canal adenocarcinoma. Comprehensive treatment, including abdominal perineal resection, radiotherapy, and chemotherapy, is important for the treatment of anal canal adenocarcinoma.